Laser capture microscopy coupled with Smart-seq2 for precise spatial transcriptomic profiling - Susanne Nichterwitz (Nature Portfolio, 2016)
Laser capture microscopy (LCM) coupled with global transcriptome profiling requires relatively large numbers of cells. Here, the authors show that LCM coupled with full-length mRNA-sequencing (LCM-seq) can sequence single cells, and that LCM-seq can provide biological insight on highly similar neuronal populations.